340 EXPANDING THE ROLE OF POEM TO ESOPHAGEAL EPIPHRENIC DIVERTICULA—FEASIBLE, SAFE AND EFFECTIVE. (14th September 2020) - Sudarshan, M; Sanaka, M; Adhikari, S; Murthy, S; Thota, P; Gabbard, S; Ahmad, U; Raja, S
Abstract:  : Epiphrenic diverticula (ED) is a rare disorder which can be associated with significant surgical morbidity. Presence of an esophageal motility disorder, often achalasia, is classically associated with ED with some arguing that symptoms are primarily attributed to the motility disorder rather than the diverticula itself. The role of peroral endoscopic myotomy (POEM) is expanding for palliation of achalasia. The objective of our study is to investigate the outcomes of POEM in patients with epiphrenic diverticula. Methods: A retrospective analysis of a prospectively maintained database was conducted in a tertiary care institution between April 2014 and July 2019. A total of 217 patients receiving a POEM during the study time period were identified with 13 patients having ED. Video recordings of POEM with and without ED were compared for technical differences. Patient demographics, prior esophageal procedures and epiphrenic diverticula characteristics were collected. Primary outcome was post-operative Eckardt scores. We also explored integrated resting pressure (IRP) on manometry, barium column height and width, complications and patient reported outcomes. Standard statistical methods were applied using R. Results: Among 13 patients with ED (median age 74.2, 69% male), 7 small and 6 large diverticula were identified. No post-operative complications were noted. The median Eckardt score significantly decreased from 8 [IQR 5–9] pre POEM to 0 [IQR 0–2] post POEM, with similar improvements in median IRPs (24.5 mmHg [IQR 16.9–31.3] vs. 4.3 mmHg [IQR 2.4–7.6], 1 min barium column height (9.2 cm [IQR 6.3–17.9] vs. 3.2 cm [IQR 0–7.1] and 1 min barium column width (3.3 cm [IQR 2.7–3.5] vs. 0.75 cm [IQR 0–3.7]. Post-operative pH studies were conducted in 7 (53.8%) patients demonstrating a DeMeester score of more than 14.72 in 5 (71.4%) patients. Conclusion: We demonstrate that POEM is technically feasible, safe and associated with excellent outcomes in patients with small and large diverticula. In our study cohort no further surgical therapy was required to address the diverticula. Reflux was managed medically. Considering its low morbidity profile POEM should be considered for therapy in selected patients with epiphrenic diverticula.